Multitasking in postanesthesia care unit following nurse interruptions, an analysis of the causes and consequences using classification tree: an observational prospective study - Charles-Hervé Vacheron; Olivier Peyrouset; Pascal Incagnoli; Virginie Charra; Stéphanie Parat; Jean-Stephane David; Alexandre Theissen; Vincent Piriou; Arnaud Friggeri (Brazilian Journal of Anesthesiology, 2023)
Background: Postanesthesia Care Unit (PACU) is an environment associated with an important workload which is susceptible to lead to task interruption (TI), leading to task-switching or concurrent multitasking. The objective of the study was to determine the predictors of the reaction of the nurses facing TI and assess those who lead to an alteration of the initial task. Methods: We conducted a prospective observational study into the PACU of a university hospital during February 2017. Among 18 nurses, a selected one was observed each day, documenting for each TI the reaction of the nurse (task switching or concurrent multitasking), and the characteristics associated with the TI. We performed classification tree analyses using C5.0 algorithm in order to select the main predictors of the type of multitasking performed and the alteration of the initial task. Results: We observed 1119 TI during 132 hours (8.5 TI/hour). The main reaction was concurrent multitasking (805 TI, 72%). The short duration of the task interruption (one minute or less) was the most important predictor leading to concurrent multitasking. Other predictors of response to TI were the identity of the task interrupter and the number of nurses present. Regarding the consequences of the task switching, long interruption (more than five minutes) was the most important predictor of the alteration of the initial task. Conclusions: By analysing the predictors of the type of multitasking in front of TI, we propose a novel approach to understanding TI, offering new perspective for prevention strategies.